Manajemen Program Tahfizh Terintergrasi Mata Pelajaran di MTs NU Al-Hidayah Kudus - Yusniawati, Yusniawati; Falah, Ahmad (Pascasarjana IAIN Kudus, 2021)
This article discusses 1) analysis of tahfizh program implementation 2) the supporting and inhibiting factors in the implementation of the tahfizh program. This type of research is a field research with a qualitative approach. The subjects in this study were students and teachers of tahfizh. Researchers used interview, observation, and documentation techniques in collecting data. The interactive descriptive analysis model was used in data analysis, namely reduction, data presentation, and verification/conclusion. The results of the study were obtained: 1) the implementation of tahfizh learning began in 2015 with an allocation of 5 hours / day except Friday. Types of components in the form of determination of materials, memorization targets, methods, assessment, infrastructure, teacher/student selection and administration funds. 2) the driving and inhibiting factors are family/community support, management, school environment, other program support activities, students' initial provision, and student environmental conditions.